Kaposiform hemangioendothelioma complicated by Kasabach–Merritt phenomenon in an infant girl - Louise Helligsø; Torben Stamm Mikkelsen; Anne‐Mette Hvas (Clinical Case Reports, 2023)
Key Clinical Message We report a successful treatment course of an infant with mediastinal Kaposiform hemangioendothelioma. As the current complex of diseases is rare and calls for highly specialized treatment, large prospective studies are lacking. This case provides an example of balanced treatment complicated by Kasabach–Merritt phenomenon, life‐threatening infections, and pericardial effusion. Abstract Kaposiform hemangioendothelioma (KHE) and tufted angioma are vascular benign tumors that can be associated with the rare condition Kasabach–Merritt Phenomenon (KMP). KMP is characterized by consumption coagulopathy with severe thrombocytopenia, hypofibrinogenemia, and elevated D‐dimer. We here report successful treatment of a female infant with a mediastinal KHE where treatment was complicated by KMP, life‐threatening infections, and pericardial effusion. Due to the absence of randomized clinical trials, there is currently no standardized treatment protocol available for KHE. In our case, the infant was treated successfully with prednisolone, vincristine, and sirolimus.